Air Pollution and Manufacturing Firm Productivity: Nationwide Estimates for China. Issue 640 (27th April 2021) - Fu, Shihe; Viard, V Brian; Zhang, Peng
Abstract: We provide nationwide causal estimates of air pollution's effect on short-run productivity for China's manufacturing sector from 1998 to 2007. Using thermal inversions as an instrument, a 1 µg/m 3 decrease in PM2.5 increases productivity by 0.82% (elasticity of −0.44). Increased hiring attenuates the elasticity to −0.17. Differential effects of a trade shock on coastal versus inner regions imply a pollution elasticity of output of 1.43. Simulating a dynamic general-equilibrium model yields an output elasticity of −0.28 with respect to PM2.5 . An exogenous 1% decrease in PM2.5 nationwide increases gross domestic product by 0.039%.